1998
DOI: 10.1016/s0954-6111(98)90105-6
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of salmeterol compared to theophylline: meta-analysis of nine controlled studies

Abstract: The aim of this study was to compare the efficacy and safety of salmeterol vs theophylline in asthma management using meta-analysis of clinical trials. Nine clinical studies, containing a total of 1330 patients, met meta-analysis inclusion criteria: randomized, controlled study, minimum 2-week treatment duration with either salmeterol or theophylline. The main outcome measurements were morning and evening peak expiratory flow rate (PEFR), morning and evening symptom scores, use of salbutamol as rescue medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 13 publications
0
21
0
3
Order By: Relevance
“…Sustained-release theophylline has little effect as a first-line controller [112] but may provide benefit, although less than that provided by long-acting inhaled b 2 -agonists [113,114], as addon therapy in patients who do not achieve control on inhaled glucocorticosteroids alone [115][116][117]. Side-effects of theophylline, particularly at higher doses (o10 mg?kg -1 body weight per day), are significant and detract from their usefulness but can be reduced by careful dose selection and monitoring, and generally decrease or disappear with continued use.…”
Section: Theophyllinementioning
confidence: 99%
“…Sustained-release theophylline has little effect as a first-line controller [112] but may provide benefit, although less than that provided by long-acting inhaled b 2 -agonists [113,114], as addon therapy in patients who do not achieve control on inhaled glucocorticosteroids alone [115][116][117]. Side-effects of theophylline, particularly at higher doses (o10 mg?kg -1 body weight per day), are significant and detract from their usefulness but can be reduced by careful dose selection and monitoring, and generally decrease or disappear with continued use.…”
Section: Theophyllinementioning
confidence: 99%
“…Meta-analyses have confirmed that adding a LABA to a dose of ICS which is failing to control asthma adequately produces a superior reduction of symptoms and use of rescue medication, and superior improvement in pulmonary function, when compared with doubling (or more than doubling) the dose of ICS [14]. A meta-analysis of nine randomized, controlled studies of salmeterol vs. theophylline, in which the majority were using inhaled corticosteroids, similarly showed salmeterol to be superior in terms C o p y r ig h t G e n e r a l P r a c t ic e A ir w a y s G r o u p R e p r o d u c t io n p r o h ib it e d of both symptoms and pulmonary function [15]. At least three studies have compared, in patients whose asthma was not adequately controlled by low dose inhaled corticosteroids, the addition of salmeterol or a leukotriene receptor antagonist [16][17][18].…”
Section: Combination Therapymentioning
confidence: 93%
“…LABA are also superior to theophylline as add-on agents. 24 The other alternative is a leukotriene antagonist. These agents are particularly useful in children, and in those who have difficulty with coordination, who prefer a tablet and who are prone to non-compliance with inhalers.…”
Section: %mentioning
confidence: 99%